Calculations of radiative heat transfer in an axisymmetric jet diffusion flame at elevated pressures using different gas radiation models. (August 2017) - Chu, Huaqiang; Consalvi, Jean-Louis; Gu, Mingyan; Liu, Fengshan
Abstract: Radiation heat transfer in axisymmetric jet diffusion flames under conditions relevant to oxygen-enriched combustion at total pressures of 1, 10, 20, and 30 atm was calculated using several gas radiation models: line-by-line (LBL), narrow-band correlated-k (NBCK), wide-band correlated-k (WBCK), full-spectrum correlated-k (FSCK), spectral-line based weight-sum-of-gray-gases (SLW), and weight-sum-of-gray-gases (WSGG). An optimized NBCK model, an optimized FSCK model, and a WBCK model were proposed and evaluated. The LBL results are used as the benchmark solution in the evaluation of other gas radiation models. The optimized NBCK model and the optimized FSCK model are much more computationally efficient than the standard implementation of these models with very little loss in accuracy. The NBCK, WBCK, and FSCK models are accurate and their normalized errors in both the radiative source term and radiative flux remain less than about 7% and display essentially no dependence on the total pressure. Whatever the pressure considered, the FSCK is found to provide accurate predictions by considering only 10 Gauss points. For the same number of gray gases, the SLW is less accurate than the FSCK, especially at pressures higher than the atmospheric pressure. However, its accuracy can be significantly improved to reach that of the FSCKby increasing the number of gray gases. The accuracy of WSGG models deteriorates somewhat with increasing the total pressure in the prediction of radiative heat flux, though it displays no significant dependence on the total pressure in the calculation of the radiative source term. The spectral line broadening has a non-negligible influence on radiative heat transfer in the jet diffusion flame. The somewhat increased inaccuracy of the WSGG model with increasing the total pressure is at least partially due to the application of the model parameters derived at 1 atm to high pressures. The normalized errors of WSGG are about 10 to 20%. The optimized FSCK model is found much more accurate than the popular WSGG model with a comparable computational efficiency and is therefore recommended for large-scale CFD applications. Highlights: An optimized NBCK, an optimized FSCK, and a WBCK model were proposed. The accuracy of seven approximate models was evaluated in a jet diffusion flame under oxy-fuel conditions between 1 and 30 atm. The accuracy of the WSGG model decreases somewhat with increasing the total pressure Spectral line broadening effect is modest, but should be taken into account. The optimized FSCK model is much more accurate than the WSGG model with comparable computational efficiency.